Study on weight of the postmortem parathyroid glands in a Bangladeshi population - Mahbub, Sabiha; Nurunnabi, Abu Sadat Mohammad; Alim, Abdul; Ahmed, Rukshana; Ara, Shamim (Journal of Dhaka Medical College, 2013)
Context: A cross-sectional descriptive type of study was designed to find out the difference in weight of the parathyroid glands of Bangladeshi people in relation to age and sex and to compare with the previous studies. Methods: This study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2008. The study was performed on 207 post mortem human parathyroid glands collected from 60 unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into three age-groups including group A (10-30 years), group B (31-60 years) & group C (61-90 years) and the weight of the parathyroids were measured and recorded. Results: The mean weight of the right superior parathyroid glands were 13.43±13.77 mg in group A, 13.86±19.15 mg in group B and 9.25±5.12 mg in group C in males and 16.00±6.69 mg in group A and 8.57±5.97 mg in group B in females respectively. The mean weight of the right inferior parathyroids were 17.78±13.94 mg, 16.75±15.67 mg and 23.00±11.53 mg in group A, B and C respectively in males and 26.00±4.18 mg in group A and 15.20±4.32 mg in group B in females. The mean weight of the left superior parathyroid glands were 13.63±6.08 mg in group A, 10.58±7.57 mg in group B and 11.00±3.74 mg in group C in males and 16.20±7.89 mg in group A and 8.29±5.47 mg in group B in females respectively. The mean weight of the left inferior parathyroid gland was 26.11±24.29 mg, 15.81±10.28 mg and 25.25±25.28 mg in group A, B and C respectively in males and 32.25±13.82 mg in group A and 13.29±5.41 mg in group B in females. No difference was found in the weight of superior parathyroid glands at right side between sexes and age groups excepting in superior and inferior parathyroid glands at left side between group A & B (p<0.05). DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15603 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 34-38